Lagoon Environments Around the World - A Scientific Perspective 2020
DOI: 10.5772/intechopen.89911
|View full text |Cite
|
Sign up to set email alerts
|

Process-Based Statistical Models Predict Dynamic Estuarine Salinity

Abstract: Climate change is increasing variation in freshwater input and the intensity of this variation in estuarine systems throughout the world. Estuarine salinity responds to dynamic meteorological and hydrological processes with important consequences to physical features, such as vertical stratification, as well as living resources, such as the distribution, abundance and diversity of species. We developed and evaluated two space-time statistical models to predict bottom salinity in Pamlico Sound, NC: (i) process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A common approach in ecohydrology, which primarily focuses on terrestrial water dynamics, is classifying streams using suites of streamflow statistics, such as mean flow and auto‐regressive lags (over time or location), as well as identifying ecological targets such as minimum base flows (Archfield et al, 2014; Kelly & Gore, 2008). Coastal salinity regimes are also classified at multiple time scales (Conrads & Darby, 2017; Durham et al, 2019), and are analyzed for important relationships between salinity and effects of freshwater streamflow and climate (Gibson & Najjar, 2000; Huang et al, 2015). Including multiple lags in these analyses “ensures representation of the month of highest influence, since a packet of freshwater reaches different locations at different times” (Gibson & Najjar, 2000, p. 1765).…”
Section: Introductionmentioning
confidence: 99%
“…A common approach in ecohydrology, which primarily focuses on terrestrial water dynamics, is classifying streams using suites of streamflow statistics, such as mean flow and auto‐regressive lags (over time or location), as well as identifying ecological targets such as minimum base flows (Archfield et al, 2014; Kelly & Gore, 2008). Coastal salinity regimes are also classified at multiple time scales (Conrads & Darby, 2017; Durham et al, 2019), and are analyzed for important relationships between salinity and effects of freshwater streamflow and climate (Gibson & Najjar, 2000; Huang et al, 2015). Including multiple lags in these analyses “ensures representation of the month of highest influence, since a packet of freshwater reaches different locations at different times” (Gibson & Najjar, 2000, p. 1765).…”
Section: Introductionmentioning
confidence: 99%
“…Working in a relatively small, tidally driven estuary in North Carolina (White Oak River), Eggleston et al (2015) used a combination of passive and active acoustic tracking of blue crabs and found that blue crabs traveled approximately 14.1 km, mainly in deeper channels, and over a period of 12–26 days from mating areas to spawning grounds. In contrast, the Croatan, Albemarle, and Pamlico Estuarine System (CAPES), the second‐largest estuarine system in the United States (Figure 1), has five narrow inlets, is wind driven and well mixed, and has a salinity gradient that drops from 35 psu at Oregon Inlet to 15–18 psu at the confluence of Croatan and Albemarle sounds (~40 km from Oregon Inlet) and to 5–7 psu near Church's Island, approximately 80 km from Oregon Inlet (Figure 1; Durham et al 2019). The CAPES is also relatively shallow (mean depth = 4.9 m) and therefore lacks the type of deepwater channels found in the Chesapeake Bay and the White Oak River that appear to serve as migration corridors for blue crabs.…”
Section: Introductionmentioning
confidence: 99%